Strategi Pengelolaan Ekowisata Berkelanjutan: Studi Kasus Kawasan Konservasi di Kalimantan Tengah - Mau, Daniel Pandu; Mau, Yesarela Pandu; Kurniansah, Rizal; Ariawan, I Wayan Adi Putra; Artana, I Wayan Arta (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aimed to formulate a sustainable ecotourism management strategy for the conservation area of Taman Wisata Alam (TWA) Bukit Tangkiling, Central Kalimantan. The area holds significant natural and cultural potential. Still, its management faces several challenges, including environmental degradation caused by illegal activities, weak inter-institutional coordination, low community participation, and suboptimal economic benefits for residents. A descriptive qualitative approach was employed. Data were collected through in-depth interviews, participant observation, field documentation, and literature review. Informants were selected purposively and included area managers, local government officials, community leaders, tourism business actors, and visitors. The findings revealed that the absence of interpretive facilities, low ecotourism literacy, and the underdevelopment of community-based tourism enterprises constituted the main obstacles to effective management. Based on these findings, the recommended management strategies include: utilizing geospatial technology for area mapping, providing digital training for local communities, diversifying tourism products, and integrating local culture into education and promotion programs. These strategies emphasize collaboration among area managers, communities, and local governments. The study’s findings are expected to strengthen community-based conservation governance and support the development of sustainable ecotourism in Central Kalimantan.